Synergistic anti-inflammatory effects of resveratrol and vitamin E in lipopolysaccharide-induced RAW264.7 cells - WANG,Na (2022)
Abstract To determine the synergistic anti-inflammatory effects of resveratrol (RES) combined with vitamin E (VE) and its mechanism. Lipopolysaccharide (LPS)-induced RAW264.7 cells were used to determine the effect of resveratrol, vitamin E and their combination on the production of cellular inflammatory mediators, including NO, IL-6, TNF-α, IL-1β, TLR4 and p-NF-κBp65. The synergistic anti-inflammatory effect of the combination was evaluated by ELISA, and the effect of the combination on the TLR4, p-NF-κBp65 and p-IĸBα pathway by Western blot. The results showed that resveratrol combined with vitamin E synergistically inhibited the production of NO, LDH, MPO and inflammatory factors IL-6, TNF-α, IL-1β and TLR4 by LPS-stimulated macrophages, and effectively inhibited the expression of TLR4, p-NF-κBp65 (P<0.01). Resveratrol combined with vitamin E have a synergistic anti-inflammatory effect. They can inhibit the expression of inflammatory mediators and further suppress the activation of TLR4, p-NF-κBp65 and p-IĸBα signaling pathway in LPS-induced RAW264.7 cell, which might provide a new effective way for inflammation treatment.